REGULACJE DOTYCZĄCE RÓWNEGO TRAKTOWANIA I ZAKAZU DYSKRYMINACJI W ZATRUDNIENIU TYMCZASOWYM - Wilczyński, Robert (Zeszyty Prawnicze, 2016)
REGULATIONS FOR EQUAL TREATMENT AND PROHIBITION OF DISCRIMINATION IN TEMPORARY EMPLOYMENT Summary The article discusses the legislation on equal treatment and non-discrimination in temporary employment in the light of the requirements of the Directive of the European Parliament and the European Council 2008/104/EC of 19 November 2008 on temporary agency work. The author recalls the legislative process related to the adoption of the Directive, in particular the legal discrepancies between the social partners and between EU countries, and analyses the content of the Directive. He then presents the provisions of the Polish labour law on equal treatment and non-discrimination. The main part of the article is devoted to a discussion of the adaptation of the legal norms on equal treatment and non-discrimination in the Act of 9 July 2003 on the employment of temporary workers and other legal acts regulating this matter to the recommendations set out in this Directive. The author analyses the current level of compliance of the Polish legislation with the requirements of the EU Directive, presents controversies in the literature, and makes recommendations de lege ferenda.